Prevalence of wrist tendonitis in sub elite badminton players - Anto, A.; Varadharajulu, G. (Journal of Pharmaceutical Negative Results, 2022)
Background: Badminton is the one of the world famous game it gives our body a rigorous workout and improve our hand, eye coordination. Wrist tendonitis is an overuse injury mainly caused by respective energy storage and release with excessive compression. The assessment of severity of tendonitis will help to decide the treatment protocol for the players and also make awareness for coach to develop a better plan for training. Method: A cross-sectional study was conducted to determine the prevalence of wrist tendonitis in sub elite badminton players. The study group consisted 80 sub elite badminton players, 45 males and 35 females both are aged between 18-26 years. The primary outcome measure used was Development and initial validation of the upper extremity functional index. Each subject was given the questionnaire and according to that the score were further evaluated. The Finkelstein test is also assessed to conform the wrist tendonitis. Result: The statistical analysis showed extremely significant relation between wrist tendonitis and sub elite badminton players with p value<0.0001 Conclusion: As a result of this study the players suffered from mild to moderate intensity of wrist pain during the game